Countering post-truths through ecopedagogical literacies: Teaching to critically read 'development' and 'sustainable development' - Misiaszek, Greg William (Educational philosophy and theory, 2020)
A key aspect of teaching 'development' is understanding the conundrums and tensions between balance and imbalance with constructs of global (all humans, all societies, all populations) and planetary (all of Earth, including humans) spheres. This article deconstructs some key tenets of populist post-truth frameworks (termed as post-truthism in this article) as affecting how development and sustainability is taught within ecopedagogies and argues for structural grounding of ecopedagogical literacy within pedagogies as increasingly imperative. Rooted in critical theories and popular education movements in Latin America, through reinvention of Freirean Pedagogy, the literacy's root word ecopedagogy is transformative teaching in which educators dialectically problem-pose the politics of socio-environmental connections through local, global, and planetary lenses. Without deepened and widened readings of development and sustainability viewed within both global and planetary spheres, in conjunction with development's effects upon local societies and ecological systems, developmental actions are unsustainable and defies the definition of development. Discussed will be the ecopedagogical tenets, including emergent ecopedagogical literacies, of critical socio-historical analysis, local and diverse epistemologies, deconstruction of pedagogies on the environment, and problem-posing one's and others' livelihood to counter post-truthism.